2003
DOI: 10.1089/088922203764969537
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Recombinant Form CRF02_AG in South America

Abstract: With the objective of monitoring the distribution of HIV-1 subtypes and circulating recombinant forms (CRFs)in South America, population-based surveillance studies were performed in seven countries. Peripheral blood mononuclear cell, filter paper, fresh blood, and cocultivation samples were collected from HIV-positive patients from Colombia, Ecuador, Peru, Bolivia, Chile, Argentina, and Uruguay, during a 7-year period(1995-2001). DNA was prepared and HIV envelope subtypes were determined by heteroduplex mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This has been stimulated by the socalled ''dollarization'' of its economy; the local currency (Sucre) is not longer accepted as a means of payment except for coinage, only US dollars are permitted as currency. Most immigrant FSW in this country were from the two neighbouring countries of Colombia and Peru, and most were in Guayaquil city (the main port of Ecuador, and a frequent commercial/tourist destination) (Carrion et al 2003). According to MoH policies, FSW are required to have periodic check-ups for STI (every 2 months for syphilis and every 4 months for chlamydia) and HIV infections (every 6 months) (IBERB 2005).…”
Section: Discussionmentioning
confidence: 97%
“…This has been stimulated by the socalled ''dollarization'' of its economy; the local currency (Sucre) is not longer accepted as a means of payment except for coinage, only US dollars are permitted as currency. Most immigrant FSW in this country were from the two neighbouring countries of Colombia and Peru, and most were in Guayaquil city (the main port of Ecuador, and a frequent commercial/tourist destination) (Carrion et al 2003). According to MoH policies, FSW are required to have periodic check-ups for STI (every 2 months for syphilis and every 4 months for chlamydia) and HIV infections (every 6 months) (IBERB 2005).…”
Section: Discussionmentioning
confidence: 97%
“…In a previous MSM prevalence study in 2000-2001 in Buenos Aires, an HIV prevalence of 13.8% was estimated and after 1-year follow-up of the same population a high HIV incidence rate of 6% per 100-person years was found. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Participants in the present cohort study were enrolled from a baseline of self-reported HIV-negative MSM. However, 66 (7.5%) HIV-positive volunteers were found among them, suggesting their lack of awareness of the risk to which they were prone not only of contracting but also of potentially transmitting the infection to their sexual partners.…”
Section: Discussionmentioning
confidence: 99%
“…This concern is further underscored by recent reports on the increasing prevalence of recombinant forms of HIV-1 in certain populations (Carrion et al, 2003;Cornelissen et al, 2000;Koulinska et al, 2001;Laukkanen et al, 2000;Montavon et al, 1999;Peeters & Sharp, 2000;Peeters et al, 2003;Yang et al, 2002;Yu et al, 2001). Already faced with the problems of antigenic drift due to the high mutation rate, the additional complexity of possible antigenic shift due to the emergence of complex HIV-1 chimeras may become an even greater impediment for the generation of prophylactic vaccines (Barouch & Letvin, 2002;Domingo et al, 1997;Heeney & Hahn, 2000;Klenerman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%